(untitled) (مجلة البحوث الأكاديمية, 2023)
This paper focuses on assessment practices in the views of Libyan preparatory and secondary school teachers and the factors that impinge on their assessment practices. This study attempts to explain the position of dynamic assessment (henceforth DA) in the Libyan Basic and Secondary Education level from the teachers’ perspectives. The aim is to uncover these teachers’ understanding of assessment and their preparedness to implement kinds of assessment congruent with the curriculum, with special reference to dynamic assessment. A total of 26 teachers responded to an open-ended questionnaire. Analysis followed an interpretative, thematic approach which yielded themes that emerged from literature and participants’ responses. Paramount of these was the testing culture that highly governed these teachers’ practices and their assessment beliefs. The paper concludes by attempting to respond to these difficulties.